Przestępczość nieletnich - pomiędzy ochroną dziecka... - Barbara Stańdo- Kawecka (Jesuit University Ignatianum in Krakow, 2017)
Since the late 1980s juvenilede linquency has become a matter of a great concernin many countries.In the last deca design if icant changes to the social attitudes towards juvenile offenders could be observed. At the same time important reforms of juvenile justice systems were carried out in the United States, Canada and some Europea ncountries. Generally,these reforms aimed at strengthening th eresponsibility of juvenile offenders for their criminal acts, especially with regard to young persistent offen dersas well a  sperpetrators of the most seriouscrimes. The Polish system of juvenile justice is based, to a large extent, on thewelfaremodel. It has recently been criticized for bothviolating the due process rules and being too soft on young offenders. It shouldbenoted, however, that severe penalties imposed on juveniles as a rule do not prevent them from further offending. Thus, early intervention strategies as well as elements of restorative justice should be considered whiled is cussing the is sue of juvenile delinquency.